The guiding logics and principles for designing emergent transdisciplinary research processes: learning experiences and reflections from a transdisciplinary urban case study in Enkanini informal settlement, South Africa - and van Breda, John; Swilling, Mark (Sustainability Science, 2019)
Transdisciplinarity is not a new science per se, but a new methodology for doing science with society. A particular challenge in doing science with society is the engagement with non-academic actors to enable joint problem formulation, analysis and transformation. How this is achieved differs between contexts. The premise of this paper is that transdisciplinary research (TDR) methodologies designed for developed world contexts cannot merely be replicated and transferred to developing world contexts. Thus a new approach is needed for conducting TDR in contexts characterised by high levels of complexity, conflict and social fluidity. To that end, this paper introduces a new approach to TDR titled emergent transdisciplinary design research (ETDR). A core element of this approach is that the research process is designed as it unfolds, that is, it transforms as it emerges from and within the fluid context. The ETDR outlined in this paper emerged through a case study in the informal settlement (slum) of Enkanini in Stellenbosch, South Africa. This case study demonstrates the context from and within which the ETDR approach and identifies a set of guiding logics that can be used to guide ETDR approaches in other contexts. The study demonstrates that the new logics and guiding principles were not simply derived from the TDR literature, but rather emerged from constant interacting dynamics between theory and practice. Learning how to co-design the research process through co-producing transformative knowledge and then implementing strategic interventions to bring about incremental social change is key to theory development in ways that are informed by local contextual dynamics. There are, however, risks when undertaking such TDR processes such as under-valuing disciplinary knowledge, transferring risks onto a society, and suppressing ‘truth-to-power’.